Explorations in legal geography: law, space and regulation - Valverde, Mariana (Routledge focus, 2026)
Addressing the issue of scale in governance, legal and extra-legal, the book draws on post-colonial studies, Indigenous geography and empirical and historical studies of the legal logics of Empire. - This book examines legal frameworks across six descending scales. Beginning with a global perspective centered on Global South viewpoints and globalization critiques, it then explores imperial legal structures. Next, it addresses the nation-state scale, predominant in both mainstream and critical legal scholarship, with particular focus on challenging notions of ethnic homogeneity. The examination continues at the local level, analyzing how various governing bodies exercise authority within their jurisdictions. It then narrows to consider "home" as both a physical and legal construct, revealing how property concepts intertwine with social relationships. Finally, it investigates the human body as a governance site through queer legal studies, queer geography, and feminist scholarship that documents how female bodies specifically have become objects of legal and extra-legal control. Concluding by considering the regulatory dilemmas that have plagued authorities as they navigate the various scales of governance considered here. - "Explorations in Legal Geography" will be of considerable interest to students and scholars of legal geography, socio-legal studies, and criminology.